Estresse e síndrome de burnout em professores do ensino superior: contexto de adoecimento e estratégias de enfrentamento - Penachi, Eliza (2018)
The present research aimed to identify and analyze strategies for coping with stress and burnout syndrome used by teachers at the Pato Branco Campus of UTFPR. The specific objectives were: To identify the occurrence and levels of stress and burnout syndrome in professors of the Pato Branco Campus of UTFPR; identify stressors reported by the research participants, and identify coping strategies for stress and burnout syndrome used by the research participants. Data were collected using the Lipp Adult Stress Symptom Inventory (ISSL), the Malasch Burnout Inventory (MBI - ED), a Structured Questionnaire and Interview. Sixty-one teachers participated in the study, 58% male and 42% female. The age ranged from 28 to 67 years and the teaching experience between 3 and 39 years. The results point to the existence of some degree of stress in 43.48% of the sample, between teachers of both sexes. Stress psychological distress is equally distributed between men and women, but physical suffering is much more evident in them than in them. Alarming levels of burnout were also found. The results obtained indicate that 26.09% of the sample did not present alteration in any of the three dimensions evaluated by MBI. Among the others, 37.68% presented alterations in one of the three dimensions of burnout and 36.23% in two or three dimensions. Alarming levels of emotional exhaustion were found in 47.82% of the sample, 26.08% in the sample, and 50.72% in the sample. The three types of coping strategies most used by participants are family support, adequate food and regular exercise, rest and leisure. It is concluded, therefore, that in addition to the cases already identified with a positive diagnosis for the burnout syndrome, 13% of the sample, the great majority of the researched population is in the process of becoming ill. Finally, considering the high levels of stress and burnout found, the results showed that only individual coping strategies are not enough to avoid the problems in the research institution.